STARS WITH HA IN EMISSION BETWEEN L338 AND L33 - IRIARTE ERRO, B; CHAVIRA, E (Observatorio Astrofísico de Tonantzintla, Pue, Pue, Mex, 1957)
A catalogue of 58 new early type stars with Ha in emission classified between l=338° and 33° is presented. The spectral types of those that could be classified are: 8 Wolf-Rayet, 2 B stars and 1 A star. The data were obtained on objective prism plates, ta
BOL OBS TONAN TACUB
Keywords: STARS, EMISSION; ASTRONOMIA Y ASTROFISICA; COSMOLOGIA Y COSMOGONIA; ESTRELLAS